Guidance on Making Compost from Organic Waste in Jatimukti Village, Jatinangor District, Sumedang Regency, West Java, Indonesia - Mochamad Suyudi; Alit Kartiwa (Research Collaboration Community (RCC), 2020)
Compost is a fertilizer that is produced from the decomposition of organic matter by active microorganisms. Jatimukti Village, Jatinangor Subdistrict, Sumedang Regency is a village that produces a lot of waste. Based on observations, the village looks suitable and has the potential to be introduced to the type of compost as organic material in farmers’ gardens. This service aims to foster and direct the people of Jatimukti Village community to have the skills to make compost from organic waste. Community service is carried out through socialization and training on composting. The demonstration of composting is done by using the composting facility that has been prepared. This dedication involves lecturers and students of the Department of Mathematics, Universitas Padjadjaran, as well as the people of Jatimukti Village. The results achieved were made of composters and compost made together, and the ways of making compost by utilizing waste in the community. After being given good and proper waste management training, the community can overcome the surrounding waste problems, and it is hoped that the community can evaluate the management that has been carried out before.